Pulling Strings with Puppet: Configuration Management Made Easy - Turnbull, James (Springer, 2017)
Competent system administrators know their success hinges upon being able to perform often tedious tasks with rigor and punctuality. Such metrics are often achieved only by instituting a considerable degree of automation, something that has become even more crucial as IT environments continue to scale both in terms of size and complexity. One of the most powerful system administration tools to be released is Puppet, a solution capable of automating nearly every aspect of a system administrator's job, from user management, to software installation, to even configuring server services such as FTP and LDAP.